Frontispiece: Building Giant Carbocycles by Reversible C−C Bond Formation. Issue 3 (12th January 2016) - Beaudoin, Daniel; Levasseur‐Grenon, Olivier; Maris, Thierry; Wuest, James D.
Abstract : Dynamic Covalent Chemistry The synthesis of giant macrocyclic hydrocarbons by a facile approach that is based on the reversible formation of carbon–carbon bonds is described by J. D. Wuest, D. Beaudoin et al. in their Communication onpage 894 ff.